Pulmonary Valve Bacterial Endocarditis in Tetralogy of Fallot - Arezoo Zoroufian; Hakimeh Sadeghian; Kyomars Abbasi; Banafsheh Alinejad (Journal of Tehran University Heart Center, 2007)
We report two cases of Tetralogy of Fallot with pulmonary valve bacterial endocarditis where one extended to the branch of pulmonary artery (PA). This is a rare occurrence. Aggressive supportive care plus early and radical surgery can be life saving.